Evaluation Of Using Liquid Smoke In Different Concentration To The Quality Physical Chemistry Beef Meatballs - A. M. S., Laksono; Miwada, I N. S.; Hartawan, M. (Jurnal Peternakan Tropika, 2017)
The study aims to analyze the quality of physical chemistry beef meatballs soaked in liquid smoke with different concentrations. Research conducted at the Laboratory of Livestock Product Technology and Microbiology, Faculty of Animal Husbandry Udayana University for two months, starting from January 30 to March 31, 2014. Liquid smoke is used from the village of Panti subdistrict Sukorambi, Jember, East Java. The meatballs were taken from the company meatballs are often consumed by the general population in Bali. The study design used completely randomized design (CRD) with five treatments and observed variables include moisture content, total acid, TBA value, phenol and water activity (?w). The results showed that the increase of liquid smoke concentration in soaking of beef meatballs could significantly increase (P<0,05) of total phenol from cow meatballs produced. The use of 2% concentration (P5) yields the highest phenol content (0.11%). Against the rancidity/Thiobarbituric Acid variables, the use of 1% liquid smoke concentration (P3) is capable of producing the lowest degree of rancidity (0.03%). While the other variables are water content, total acid and water activity, the use of different concentrations of liquid smoke, does not result in a significantly different value (P> 0.05). Based on the results of the research can be concluded the use of liquid smoke at a concentration of 1% capable of producing cow meatballs with the lowest rancidity. Keywords : Liquid Smoke, BeefMeatballs , Concentration, Quality